Insomnia and circadian rhythm: a bibliometrics study and visualization analysis via CiteSpace - He, Qing-Yun; Dai, Ning; Mao, Meng; Ma, Jie; Wen, Qiao; Song, Dan-Dan; Liu, Yan; Li, Feng (Frontiers in Neurology, 2023)
Objective The present study aimed to use CiteSpace to analyze the status of insomnia and circadian rhythm, identify the hot spots and trends, and provide a basis for future study. Method The Web of Science database was searched for studies related to insomnia and circadian from its inception to 14 April 2023. CiteSpace was used to generate online maps of collaboration between countries and authors and revealed hot spots and frontiers in insomnia and circadian rhythm. Results We searched 4,696 publications related to insomnia and circadian rhythm. Bruno Etain was the most prolific author with most publications, i.e., with 24 articles. The USA and the University of California were the leading country and the top institution in this field of study, with 1,672 and 269 articles, respectively. There was active cooperation between institutions, countries, and authors. Hot topics focused on circadian rhythm sleep disorders, circadian clock, light therapy, melatonin, and bipolar disorder. Conclusion Based on the CiteSpace results, we recommend a more active collaboration between various countries, institutions, and authors to conduct clinical and basic research related to insomnia and circadian rhythm. Ongoing research focuses on the interaction of insomnia with circadian rhythms and the corresponding pathways of clock genes and by extension, the role of circadian rhythms in disorders such as bipolar disorder. Modulation of circadian rhythms may be a hot spot for future insomnia therapies (such as light therapy and melatonin).